Assessment of shale gas potential of Paleozoic shales from Western Peninsular Malaysia - Syed, I. (European Association of Geoscientists and Engineers, EAGE, 2021)
Gas extraction through a specific shale formation mostly relies on its gas storage capacity. In unconventional system i.e., shale gas, gas is largely stored in the pores spaces and adsorbed on the surface of mineral and organic matter particle. Thus, sorption properties along with mineralogical and geochemical characterization can deliver valuable information on the gas storage capacity of a specific shale formation. Paleozoic black shale-bearing formations are widespread in WP Malaysia. However, there is a lack of published literature present on WP Malaysia shale formations regarding the methane adsorption capacities at reservoir T&P, geochemical and mineralogical analysis which reveals their potential as shale gas reservoirs. Therefore, sixteen samples from seven Paleozoic formations of different geological ages (Silurian-Permian) were collected. These Paleozoic Formations are exposed at Langkawi, Kedah, Perlis, and Perak state of WP Malaysia and grouped into four divisions on the basis of their age i.e., Silurian-Devonian (Baling and Bendang Riang Formations), Devonian (Sanai and Timah Tasoh Formations), Carboniferous (Kubang Pasu, Sanai and Batu Gajah Formations), and Permian (Kubang Pasu Formation). For the assessment of shale gas potential, a comparison of key major properties of the WP Malaysia shale to the world-renowned potential gas shale reservoirs was also examined. Â© EAGE Asia Pacific Virtual Geoscience Week 2021. All rights reserved.